Anesthetic challenges in difficult airway in a patient with maxillary carcinoma: A case report - Kamala Karki; Prashant Pant; Suchit Thapa Chhetri; Sumit Kumar Sah; Kanchan Bogati (Clinical Case Reports, 2023)
Key Clinical Message Airway management in patients with maxillary carcinoma presents unique challenges. To ensure safety, a tailored and collaborative approach is essential. This is a case where anesthetic plan of awake fiberoptic oral endotracheal intubation was chosen.